The Role of AI in Modern Healthcare Systems - Jaspreet Kaur; Sukhpreet Singh (International Journal of Bioinformatics and Computational Biology, 2025)
In the Indian pandemic, several issues in the healthcare system have brought to the forefront the imperative of hospitals shifting from manual medical records to computerized healthcare information systems. These solutions offer an effective method for integrating computer-based decision support tools and communicating e-healthcare information. With increasing dependence on AI-based solutions, a strong IT infrastructure is essential for improving healthcare quality, data security, and controlling increasing medical expenses. Advances in communication technology and networking are fundamental to the modernization of healthcare services and addressing both patients' and providers' needs. An AI-powered hospital system is not only necessary but also feasible despite its challenges. This paper discusses the uses of IT in hospitals and medical environments. They could improve clinical judgment, the recording of imaging and medical history, reduce duplication of diagnostic tests, and enhance reliability on medication with improved use of healthcare resources, and enhanced preventive health programs
Keywords: Clinical decision support systems; Electronic health records (EHR); Healthcare IT Infrastructure; Medical Data Management; artificial intelligence in healthcare